Assessment of Salivary Gland Function Using Salivary Scintigraphy in Pre and Post Radioactive Iodine Therapy in Diagnosed Thyroid Carcinoma Patients - Badam, Raj Kumar (J Clin Diagn Res, 2016)
INTRODUCTION: Thyroid carcinoma represents less than 1% of all cancers. The first line of treatment for thyroid cancer is partial/total thyroidectomy. High-dose Iodine(131) therapy using Iodine radioisotopes is commonly used in patients with well differentiated thyroid carcinoma after total thyroidectomy. In this process, the non-thyroidal tissues, such as, salivary gland, stomach and breast tissues also take up radioactive iodine. Salivary gland scintigraphy is widely accepted as a sensitive and valid method for evaluation of salivary gland dysfunction after Radioactive Iodine(131) Therapy (RIT). AIM: To assess and compare the salivary flow rates, relative uptake and ejection fractions in parotid and submandibular glands just before and one month after Iodine(131) therapy. MATERIALS AND METHODS: The study was conducted on 24 patients diagnosed with well differentiated thyroid carcinoma who underwent partial/total thyroidectomy and were due for radioactive iodine therapy. These patients were divided into two groups based on the lesion based dosimetry (Group A: 60-100Gy; Group B: 100-150Gy). Salivary gland assessment was done by salivary gland scintigraphy before and after RIT. STATISTICAL ANALYSIS: The data collected was tabulated and statistically analysed using SPSS software version16 using paired t-test and individual sample t-test. RESULTS: A statistically significant difference in the uptake percent and ejection fraction percent in the parotid and submandibular glands before RIT and one month after RIT was observed in the study. CONCLUSION: We inferred from the study that there was an overall decrease in uptake percent and ejection fraction percent one month post RIT in both parotid and submandibular glands. Also, a statistically significant difference was noted in the uptake and ejection fraction percent between Group A and Group B concluding the fact that the damage is dose related.